Разложите на множители
28x3 + 3x2 + 3x + 1

ykub321 ykub321    2   29.06.2019 16:26    2

Ответы
Sokolova2327 Sokolova2327  23.07.2020 16:16
28х³+3х²+3х+1 = 27х³ + (х³+3х²+3х+1) = (3х)³ + (х+1)³ =
= (3х+(х+1))((3х)²-(3х(х+1))+(х+1)² = (3х+х+1)(9х²-3х²-3х+х²+2х+1) =
= (4х+1)(7х²-х+1)
ПОКАЗАТЬ ОТВЕТЫ
valerysidochenozpzmu valerysidochenozpzmu  23.07.2020 16:16

(4х+1)(7х²-х+1)

Объяснение:    28х³+3х²+3х+1 = 27х³ + (х³+3х²+3х+1) = (3х)³ + (х+1)³ =  

= (3х+(х+1))((3х)²-(3х(х+1))+(х+1)² = (3х+х+1)(9х²-3х²-3х+х²+2х+1) =  

= (4х+1)(7х²-х+1)

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра